Civic Education and Digital Technology: A Literature Review - Rahayu, Yayuk Muji; Devi, Lathifah Sandra; Abidin, Raistin Nur; Marlina, Lina (CV. Rayyan Dwi Bharata, 2025)
Digital transformation has brought significant changes in the world of education, including in the learning of Civic Education (Civics Education). This journal aims to examine in depth the relationship between the use of digital technology and the strengthening of civic values, especially Pancasila values, in the learning process. This research uses a qualitative approach with a library research method, which analyzes various scientific literature, research reports, educational policies, and other relevant sources published in the last decade. The results of the study indicate that the integration of information technology in Civics learning opens up great opportunities to create a more participatory, interactive and contextual learning process. Digital technology not only improves learners' conceptual understanding, but can also strengthen the internalization of Pancasila values through innovative learning media such as videos, simulations, online forums, and digital projects. However, the implementation of technology also faces various challenges such as limited infrastructure, digital divide, and low digital literacy among educators and learners.